HUBUNGAN KREATIVITAS GURU DALAM PENGELOLAAN KELAS TERHADAP PEMAHAMAN MATERI SISWA KELAS III UPTD SDI KUANINO 2. - Getreda Y. Beama; Heryon B. Mbuik; Hingrida M. A. Hendrik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher creativity in classroom management is considered an essential factor in creating meaningful learning experiences and improving students' understanding of learning materials. However, classroom instruction in elementary schools is often still teacher-centered, resulting in limited student engagement and suboptimal learning outcomes. This study aimed to examine the relationship between teacher creativity in classroom management and students' understanding of learning materials among third-grade students at UPTD SDI Kuanino 2. The study employed a quantitative approach using a correlational research design. The population consisted of 21 third-grade students, all of whom were selected as the research sample through total sampling. Data were collected using Likert-scale questionnaires measuring teacher creativity in classroom management and students' understanding of learning materials. The research instruments were tested for validity and reliability before data collection. Data analysis included descriptive statistics, the Shapiro–Wilk normality test, and Spearman Rank correlation analysis because the data were not normally distributed. Descriptive analysis indicated that teacher creativity in classroom management was in the good category (77.56%), while students' understanding of learning materials was also categorized as good (76.25%). The findings revealed a positive and significant relationship between teacher creativity in classroom management and students' understanding of learning materials. These findings indicate that improving teacher creativity in managing classroom learning contributes to better student understanding. Therefore, teachers are encouraged to continuously develop innovative classroom management strategies to enhance learning quality in elementary schools.